Front Cover: Active‐ion‐gated room temperature acetone gas sensing of ZnO nanowires array (EXP2 6/2022). Issue 6 (18th December 2022) - Guo, Junmeng; Gan, Jiahui; Ruan, Haoran; Yuan, Xiaobo; Kong, Chuiyun; Liu, Yang; Su, Meiying; Liu, Yabing; Liu, Wei; Zhang, Bao; Zhang, Yongle; Cheng, Gang; et al.
Abstract : Gang Cheng and co‐workers firstly report an active‐ion‐gated strategy to active room temperature (RT) acetone sensing of metal oxide semiconductors (MOS). The strategy presents high performance and low power consumption, which paves the way for boosting the RT gas sensing performance of traditional MOS by customizing specific ions with various discharge gas atmosphere.